When central banks buy corporate bonds: Target selection and impact of the European Corporate Sector Purchase Program - R.J. Galema; S. Lugo (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
In March 2016 the European Central Bank (ECB) announced the Corporate Sector Purchase Program (CSPP) as part of its expanded asset purchase program. Using hand-collected, weekly lists of bonds purchased and held under the CSPP, we investigate the drivers of the purchase decisions and the impact of the program on the financing decisions of targeted firms. We find that, consistent with the goal of decreasing credit premia while minimizing price distortions, purchases of eligible bonds characterized by both higher credit risk and higher liquidity are more likely and more timely. Bonds issued by firms more likely to face difficulties in tapping the credit market directly are also more likely to be purchased. The CSPP appears effective in alleviating these difficulties. Firms targeted by the program increase their amount of bonds outstanding significantly more than non-targeted eligible issuers; the effect is mostly driven by companies making limited use of market debt before the start of the program. However, no difference is found in the variation of total debt between targeted and non-targeted eligible issuers. Together, these results suggest that the CSPP has favored the substitution of bonds for other forms of debt capital.
Keywords: 330